CLIL In Senior High School: Empowering English Language Teaching and Learning in Merdeka Curriculum - Muhammad Kholili; Sri Rachmajanti; Anik Nunuk Wulyani (Didaktika: Jurnal Kependidikan, 2024)
Content and Language Integrated Learning (CLIL), is an approach that focuses on both content and language learning. The research design was a mixed method, Exploratory Sequential Research, which combined quantitative and qualitative research. A total of 71 students in one of the senior high schools in Gresik, East Java participated as research participants. They consisted of 39 students in the experimental group and 32 students in the control group. The results showed that there was a significant effect of CLIL on students' learning achievement in Merdeka Curriculum. The first theme used to determine students' initial experience. The research showed that students initially had difficulties in understanding biology concepts and using English academically. However, CLIL proved to be engaging and motivating, improving content understanding as well as language skills. Students were able to express complex biology concepts better, although challenges in academic writing and communication remained. They reflected on the need for real-world based learning and additional English lessons. Positive experiences in CLIL classes also encourage self-regulation for academic and career development.